Catalytic synthesis of nanocellulose from oil palm empty fruit bunch fibres / Mazlita Yahya - Mazlita , Yahya (2016)
Currently, Malaysia has substantially increased its reputation as a country developed for palm-based lignocellulosic biomass. Oil palm biomass is composed of cellulose, hemicellulose, and lignin. Generally, oil palm biomass can be divided into three categories: (i) oil palm frond (OPF), oil palm trunk (OPT) and empty fruit bunches (EFB) fibres. The presence of high cellulose content in oil palm biomass is potentially converted to nanocellulose, which is a promising bio-polymer that useful for various industrial applications (personal cares, chemicals, foods, pharmaceuticals and bio-composites). Objectives of this project are to study the effectiveness of catalytic conversion of oil palm biomass (EFB) into nanocellulose by using chemical route (inorganic acid: H2SO4 and inorganic salt: Ni (NO3)2) and also to optimize the nanocellulose yield by study different reaction parameters (reaction temperature ,reaction time and acidity of catalyst). Finally the objectives is to determine the physicochemical properties of produced nanocellulose by using Thermogravimetric Analyzer (TGA) and Derivatives Thermogravimetric(DTG), X-Ray Diffractometer (XRD), Fourier Transform Infrared (FTIR), High Resolution Transmission Electron Microscope (HR-TEM), Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy(AFM), and Particle Size Analyzer (PSD) techniques. Nanocellulose was successfully yielded from oil palm biomass (EFB) via and strong acid hydrolysis (H2SO4) and Ni-salt catalyzed hydrolysis which annotated as SA-NC and Ni-NC respectively. The mild acid nickel-salt catalyzed hydrolysis capable to selectively depolymerized amorphous regions of cellulose and retained its crystalline region, thus improving the crystallinity index of the Ni-NC up to 80.75% compared to SA-NC (73.17%). The FTIR analysis confirmed that the basic cellulose structure of inorganic Ni-salt and H2SO4 treated products was maintained and no derivative was formed. Furthermore, FESEM images clearly display that outer layer (waxes, pectins and fats) of EFB fibres has been removed after pretreatment process. The chemical pretreatment methods was performed followed by acid hydrolysis process to produce nano-scale dimension (SA-NC and Ni-NC). Chemical pretreatment process was executed in order to enhance both strong and mild acid hydrolysis process (SA-NC and Ni-NC). HR-TEM and AFM analyses showed that acid hydrolysis was capable to depolymerize cellulose micro-chain into average nano-dimensions in fibres length ( < 700 nm) and fibres width dimension (< 50 nm). In addition, PSD results clearly showed the particle sizes had been reduced from EFB fibres(<5500 nm) to SA-NC and Ni-NC(<90.00 nm). This study concluded that Ni-salts is an efficient and selective catalyst for the hydrolysis of cellulose with high simplicity in operation as compared to inorganic acid (H2SO4). Optimization reaction conditions (reaction temperature, reaction time, and acidity of catalyst) were performed in order to obtain the optimized condition for nanocellulose production. Based on the reaction model generated from Response Surface Methodology-Face Central Composite Design (RSM-FCCD), the predicted nanocellulose yield was 81.40 % (60min, 45 °C, pH 3). Meanwhile, the experimental value (81.37 %) achieved was reasonably near to the predicted value generated from the model. It can be concluded that the generated model is near to predictability and close to precision for the nanocellulose yield in the experimental conditions used. In summary from the results above, it shows that nanoscale of cellulose (Ni-NC and SA-NC) was successfully produced, characterized as well as optimized from oil palm biomass (EFB) via Ni-Salt and H2SO4 catalyzed treatment.